BELAJAR DARI MONYET - Rokhmaniyah Rokhmaniyah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
The Monkey Training Academy indirectly implements progressive paedagogic principles. The Monkey Training Academy also applies the four pillars of education according to UNESCO (learning to know, learning to do, learning to live with others, and learning to be someone). This literature research can inspire educators to be creative. Sources of research data in the form of books "Learning from Monkey" by Rung Kaewdang, 2002. Education is implemented with cheap and applicable able to print skilled learners. However, in this era not only skills are targeted, but also creative and innovative learners. Privileges in APM are the patience of a teacher facing various learners' character and can turn it into a better direction.